2015
DOI: 10.1016/j.eururo.2014.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Castration-resistant Prostate Cancer Treatments Administered as Third or Fourth Line Following Failure of Docetaxel and Other Second-line Treatment: Results of an Italian Multicentre Study

Abstract: It is debated which sequence of treatments to adopt after docetaxel. Our data do not support the superiority of any of the three new agents in third-line treatment, regardless of the previously administered new agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 23 publications
3
48
0
1
Order By: Relevance
“…102 It should be mentioned that ASIs might have some effect after progression on cabazitaxel, and patients whose health status descends to "frail" as a result of progression of the disease could still benefit from subsequent treatment with ASIs. 103 Radium-223 is considered an appropriate option for patients with symptomatic bone and non-visceral metastases. Comparable toxicity when using radium-223 with other ASIs was reported, 104 and a preliminary report from a phase 1/2a study showed that radium-223 with docetaxel had greater percentage decline in total alkaline phosphatase and in bone formation markers, bone alkaline phosphatase and P1NP, than the treatment with only docetaxel.…”
Section: Cross-resistance Between Classes Of Agentsmentioning
confidence: 99%
“…102 It should be mentioned that ASIs might have some effect after progression on cabazitaxel, and patients whose health status descends to "frail" as a result of progression of the disease could still benefit from subsequent treatment with ASIs. 103 Radium-223 is considered an appropriate option for patients with symptomatic bone and non-visceral metastases. Comparable toxicity when using radium-223 with other ASIs was reported, 104 and a preliminary report from a phase 1/2a study showed that radium-223 with docetaxel had greater percentage decline in total alkaline phosphatase and in bone formation markers, bone alkaline phosphatase and P1NP, than the treatment with only docetaxel.…”
Section: Cross-resistance Between Classes Of Agentsmentioning
confidence: 99%
“…However, these finding might not apply to DCT considering that men receiving AA before DCT are more likely to progress on DCT and less likely to achieve a PSA response that AA-naïve patients [70,[74][75][76][77][78]. In addition, large multicenter studies failed to show any signifcant difference in the clinical outcomes of third line treatment with AA, ENZ or CZT regardless of previous therapy delivered [79], whereas in a less advanced treatment setting, the prospective evidence from the recent TERRAIN trial support the use of ENZ rather than bicalutamide in patients with asymptomatic or midly symptomatic CRPC [80]. Supplemental Figure 3 shows options of targeting CRPC according to the activation of AR.…”
Section: Sequential Administration Of New Agents In Crpcmentioning
confidence: 86%
“…Since the advent of abiraterone and enzalutamide, the use of cabazitaxel has declined. Intriguingly, some but not all retrospective studies suggest that cabazitaxel followed by androgen axis inhibitors might lead to improved outcomes compared with androgen axis inhibitors followed by cabazitaxel [5,6]. Another piece in the puzzle is provided by retrospective studies suggesting that cabazitaxel may retain substantial activity even after docetaxel and novel androgen inhibitors, while docetaxel appears to show poorer activity after androgen inhibitors [7].…”
mentioning
confidence: 99%
“…Then, in 2012, Rolle et al [5] described the sliding technique, a modification of the circumferential graft that consists of a double dorsal-ventral patch and should therefore…”
mentioning
confidence: 99%